β subunits influence the biophysical and pharmacological differences between P- and Q-type calcium currents expressed in a mammalian cell line - Moreno, Herman (The National Academy of Sciences of the USA, 1997)
Human epithelial kidney cells (HEK) were prepared to coexpress α1A, α2δ with different β calcium channel subunits and green fluorescence protein. To compare the calcium currents observed in these cells with the native neuronal currents, electrophysiological and pharmacological tools were used conjointly. Whole-cell current recordings of human epithelial kidney α1A-transfected cells showed small inactivating currents in 80 mM Ba(2+) that were relatively insensitive to calcium blockers. Coexpression of α1A, βIb, and α2δ produced a robust inactivating current detected in 10 mM Ba(2+), reversibly blockable with low concentration of ω-agatoxin IVA (ω-Aga IVA) or synthetic funnel-web spider toxin (sFTX). Barium currents were also supported by α1A, β2a, α2δ subunits, which demonstrated the slowest inactivation and were relatively insensitive to ω-Aga IVA and sFTX. Coexpression of β3 with the same combination as above produced inactivating currents also insensitive to low concentration of ω-Aga IVA and sFTX. These data indicate that the combination α1A, βIb, α2δ best resembles P-type channels given the rate of inactivation and the high sensitivity to ω-Aga IVA and sFTX. More importantly, the specificity of the channel blocker is highly influenced by the β subunit associated with the α1A subunit.